Novel Index to Quantify the Risk of Surgery in the Setting of Adult Spinal Deformity: A Study on 10, 912 Patients From the Nationwide Inpatient Sample. Issue 7 (August 2017) - Diebo, Bassel G.; Jalai, Cyrus M.; Challier, Vincent; Marascalchi, Bryan J.; Horn, Samantha R.; Poorman, Gregory W.; Bono, Olivia J.; Cherkalin, Denis; Worley, Nancy; Oh, Jason; Naziri, Qais; Spitzer, Allison; et al.
Abstract : Study Design: Retrospective review of the Nationwide Inpatient Sample from 2001 to 2010, a prospectively collected national database. Objective: Structure an index to quantify adult spinal deformity (ASD) surgical risk based on risk factors for medical complications, surgical complications, revisions (R), mortality (M) rates, and length of hospital stay. Summary of Background Data: Evidence supporting ASD surgery cost-effectiveness and anticipating surgical risk is critical to evaluate the risk/benefit balance of such treatment for patients. Materials and Methods: Discharges ages 25+, 4+ levels fused, diagnoses specific for scoliosis, and refusions. Five multivariate models determined independent risk factors that increased the risk of ≥1 for medical complications, surgical complications, R, M, and length of hospital stay. Models controlled for age, sex, race, revision status, surgical approach, levels fused, and osteotomy utilization. Odds ratios (ORs) were weighted using Nationwide Inpatient Sample weight files and based on their predictive category: 2 times for revision predictors and 4 times for mortality predictors. Predictors with OR≥1.5 were considered clinically relevant. Fifty points were distributed among the predictors based on their accumulative OR to establish a risk index. Results: A total of 10, 912 ASD discharges were identified (mean age: 62 y; 73% females; 14% revision cases). The structured risk index incorporated the following factors based on accumulative ORs: pulmonary circulation disorder (42.05), drug abuse (21.86), congestive heart failure (15.25), neurological disorder (17.31), alcohol abuse (13.24), renal failure (11.64), age>65 (12.28), coagulopathy (11.65), level +9 (6.7), revision (3.35), and osteotomy (3). These risk factors were scored: 14, 7, 5, 5, 4, 4, 4, 4, 2, 1, 1, respectively. Three risk thresholds were proposed: mild (0–10), moderate (10–20), severe >20/50 points. Conclusions: This study proposes an index to quantify the possible risk of morbidity before ASD surgery that will help patients, health insurance companies, and socioeconomic studies in assessing surgical risk/benefits. Level of Evidence: Level III.